Building China’s National Carbon Market That Serves Carbon Peaking and Carbon Neutrality Goals - Xin ZHANG (Chinese Journal of Urban and Environmental Studies, 2022)
This paper summarizes the new progress in building China’s national carbon market since 2020, and analyzes the connotation of China’s carbon peaking and carbon neutrality goals (“dual carbon” goals) and its significance to socio-economic development in China. Through case analysis, this paper expounds the role of China’s recent carbon trading activities in promoting the transition toward green and low-carbon socio-economic development. On that basis, this paper conceives a top-level design for building the national carbon market that serves the “dual carbon” goals: building and improving the national carbon market that fundamentally serves as an emission reduction tool, developing the institutions and systems of the national carbon market with a focus on emission cap, creating a multilevel and diversified carbon trading scheme centered on the national carbon market, exploring a mechanism that takes carbon emission reduction as the core and promotes the synergistic effect of the carbon market with other environmental rights trading markets, and pursuing the healthy and orderly development of carbon finance that aims to serve carbon emission reduction.